Acute high‐intensity football games can improve children's inhibitory control and neurophysiological measures of attention. (24th June 2019) - Lind, Rune Rasmussen; Beck, Mikkel Malling; Wikman, Johan; Malarski, Krzysztof; Krustrup, Peter; Lundbye‐Jensen, Jesper; Geertsen, Svend Sparre
Abstract : Recent studies suggest that a single bout of exercise can lead to transient performance improvements in specific cognitive domains in children. However, more knowledge is needed to determine the key exercise characteristics for obtaining these effects and how they translate into real‐world settings. In the present study, we investigate how small‐sided football games of either high‐ or moderate‐intensity affect measures of inhibitory control in a school setting. Eighty‐one children (mean age 11.8, 48 boys) were randomly allocated to three groups performing 20‐minute of high‐intensity small‐sided real football games (SRF), moderate‐intensity small‐sided walking football games (SWF) or resting (RF). Behavioral measures of inhibitory control and neurophysiological measures of attention (P300 latency and amplitude) were obtained during a flanker task performed at baseline and 20 minutes following the intervention. Retention of declarative memory was assessed in a visual memory task 7 days after the intervention. Measures of inhibitory control improved more in children performing SRF compared to SWF 19 ms, 95% CI [7, 31 ms] ( P = 0.041). This was paralleled by larger increases in P300 amplitudes at Fz in children performing SRF compared both to RF in congruent (3.54 μV, 95% CI [0.85, 6.23 μV], P = 0.039) and incongruent trials (5.56 μV, 95% CI [2.87, 8.25 μV], P < 0.001) and compared to SWF in incongruent trials (4.10 μV, 95% CI [1.41, 6.68 μV], P = 0.010). No effects were found in measures of declarative memory. Together this indicates that acute high‐intensity small‐sided football games can transiently improve measures of inhibitory control and neurophysiological correlates of attention. Intense small‐sided football games are easily implementable and can be employed by practitioners, for example, during breaks throughout the school day.